A CLINICO COMPARATIVE STUDY OF PANCHASAMA CHOORNA WITH AND WITHOUT VALUKA SWEDA IN AMAVATA W.S.R. RHEUMATOID ARTHRITIS - Prasad , Nagendra (Journal of Ayurveda and Holistic Medicine (JAHM), 2021)
Background: Amavata which can be compared to Rheumatoid arthritis is a clinical condition where low digestive power plays an important role. Panchasama choorna helps in the management of Amavata by increasing digestive power, clearing the channels of circulation, reduces inflammation and pain when administered with fomentation. Objectives: 1.To compare the efficacy of trial drug Panchasama choorna individually as well as with valuka sweda (fomentation by sand bolus). 2. To establish a safe, economical and effective medication for Amavata without side effect. Method: In this study 30 patients were selected satisfying the inclusion criteria and randomly divided into two groups. In Group A– Panchasama choorna 4gms TID was administered for 30 days with Luke warm water. In Group B – Panchasama choorna 4gms TID with Luke warm water was administered for 30 days with valuka sweda for 15 days. Severity of the disease was assessed based on selected subjective and objective parameters. Results: After trial, it was observed that better and sustained relief with respect to all the signs and symptoms were observed in group B which is treated with combined therapy. Overall assessment shows marked, moderate, mild improvement and unchanged as 20%, 46.7%, 26.7% & 6.7% respectively among group B patients. Conclusion: The drug Panchasama choorna was found to be highly significant in providing symptomatic relief when administered along with valuka sweda